Verification of electronic device technology for measurement and evaluation of thermal exposure of fire fighters and members of rescue teams - Šárka Bernatíková; Hana Tomášková; Marek Bužga; Zdeněk Jirák; Petr Novák; Ján Babjak; Tomáš Kot; Václav Krys; Ladislav Jánošík (Medycyna Pracy, 2018)
Background The work of members of rescue teams could be associated with very high physical and thermal loads. If not timely interrupted, any extreme labour-thermal load may lead to a failure of the body and fatal collapse. This risk may be significantly reduced by devices that monitor the response of the body during the intervention and inform rescuers about the need to interrupt the exposure when the critical value of the reference indicator is achieved. The aim of the study was to test the correlation between the data of the newly developed device for signaling the strain of rescuers and the indicators of physiological response of the body.